(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
The available literature on arthroplasty for the ankylosed hip joint remains highly relevant for the study of etiopathogenesis, clinical features, diagnostic methods, selection of surgical treatment, and staged postoperative rehabilitation of patients.